ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЛАРЫНДА ЫРЫМ ҲӘМ ИСЕНИМЛЕР - Палымбетов, К.С. (FAN va JAMIYAT, 2023)
This article discusses mythological views, various beliefs and superstitions in the composition of the Karakalpak folk epics, talks about their epic character in the development and enrichment of the plot, the change in the course of events and other phenomena. Some of these beliefs are the month of "safar", during which one cannot travel; in case of a hike one needs to take bread with himself; words of blessing or damnation. The article analyzes the events and phenomena associated with these beliefs from a scientific point of view by means of examples.